Relative Importance of Habitat Characteristics and Interspecific Relations in Determining Terrestrial Carnivore Occurrence - Rich, Mackenzie; Thompson, Cassandra; Prange, Suzanne; Popescu, Viorel D. (Frontiers in Ecology and Evolution, 2018)
Carnivores act as top-down regulators in terrestrial ecosystems, and their occurrence and relative abundance is a result of complex interactions between food and habitat availability, human pressure (e.g., trapping, hunting, roadkill) and intraguild interactions (competition, predation). Eastern United States has a long history of human impact, which resulted in an altered carnivore community. Specifically, Ohio presents an interesting case for evaluating the relative roles of interspecific relations and habitat characteristics for shaping the carnivore community, as its carnivore community has a unique dynamics and composition: invasive coyote and red fox (Vulpes vulpes), and native bobcat (Lynx rufus), currently recovering and expanding its range, gray fox (Urocyon cinereoargenteus) declining at a fast pace, and the generalist raccoon (Procyon lotor) and Virginian opossum (Didelphis virginiana). We used 50 camera traps to collect presence/absence data in southeastern Ohio, USA. We hypothesized potential interactions between the six carnivores, and used land cover variables, as well as occupancy probabilities of interacting species, to parameterize to single-species occupancy models. We found that landscape composition at three different scales (500m and 1000 m buffer around camera locations, and 3x3 km grid cell) had little effect on species occurrence. We identified strong negative interspecific relations between carnivores, with bobcat occurrence being influenced by presence of coyotes, red fox occurrence by gray foxes, and raccoon occurrence by Virginia possums. While these findings cannot discriminate between habitat partitioning (spatial or temporal) and competition (direct or interference), they lend support to complex dynamics between invasive coyotes and red foxes and recovering (bobcat) and declining (gray fox) native carnivore species. In particular, the negative relation between the apex predator in our system, C. latrans, and L. rufus, raise further questions on whether direct competition from coyotes has the potential to slow bobcat population recovery. In the context of regulated trapping (ongoing for gray fox and proposed season for bobcat), a better understanding of the carnivore intraguild relations can inform management and conservation actions targeted at minimizing the impact of competition on at-risk native species from non-native species.